Saint Thomas d’Aquin dans la théologie de Péter Pázmány - Szabó, Ferenc (Verbum – Analecta Neolatina, 2004)
The Jesuits’ Ratio Studiorum ordered to follow St. Thomas’s theology. Between 1603-1607, at the University of Graz, Péter Pázmány S.J. gave lectures on St. Thomas’s Summa Theologie and commented on its most important issues. St. Thomas thoroughly studied the problem of faith (de Fide) and explained the questions of grace and liberty (de auxiliis) debated by the Jesuits and the Dominicans. He found a fine balance between Banezianism and Molinism through the following main principle: grace intensifies liberty, that is, God does not act on behalf of us but makes us act.